UPAYA MENINGKATAN KOPETENSI PEDAGOGIK GURU MELALUI SUPERVISI AKADEMIK DI SMP NEGERI 8 KETAPANG - Harto, Budi (Jurnal Kajian Pembelajaran dan Keilmuan, 2020)
AbstractThis research aims to know the proer steps in achieving academic supervision thus being able to improve teacher pedagogical competencies primarily in the learning process that will eventually affect the quality of education. So resarch is done on two cycles. On every cycles has differentplanning, implementation, observation, and reflection. The principal and teacher’s research subjects. The principal with his academic supervision act, while the 8 Ketapang public school teacher of the country was both object and subject to the administering of academic supervision. The technique of data collection through class supervision stage in the learning process, to record importand events related to research particularly at the time of the learning process. Research shows that teacher’s ability to implement the learning process experiances an increase of percentage per step from cycle I to an average of 63% (enough) and to cycle II to an average of 68% (good).there is a 5% increase in teacher’s ability in this cycle I. There is a significant increase in the initial conditions of the school whwn compared with the final conditions of the second cycle II. Teacher punctuality gets into the classroom increases 48%, media utilization increases 32%, variative methods increase 31%, and study strategies increase 36%.Keywords: Pedagogical Competencies, Academic Supervision, and Improved Middle Education Quality (SMP).